What the Camorra is. The first part of the 1993 Report of the Parliamentary Anti-mafia Commission (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The first part of the Report on the Camorra published by the Parliamentary Anti-Mafia Commission in 1993 is offered here. The article introduces the text by examining its salient points, focusing on the continuity features of the camorristic phenomenon and the exceptional level of dangerousness it assumed between the 1970s and 1990s.
Keywords: camorra; Campania; prison; Violante; Cutolo